Sosialisasi Dampak dan Pengaruh Internet Bagi Pelajar di Panti Asuhan Aisyiyah Putra Padang - Elizamiharti; Nelfira; Nur Azizah; Yessy Prima Putri; Sri Restu Ningsih (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The rapid development of technology, if we don't follow it, it will make us left behind in facing the times, especially in the field of education. For this reason, it is necessary to socialize to students at the Orphanage, how to use the internet wisely. The purpose of this Community Service (PKM) is outreach to provide increased knowledge about the impact and influence of using the internet for students. This activity was carried out at the Aisyiyah Putra Orphanage in Nanggalo District, Padang City. The method used in carrying out this activity is the lecture method and the question and answer method and quizzes. The material provided is in the form of socialization on how to use the internet wisely by knowing its positive and negative impacts and their influence on students. The result of this PKM activity is an increase in technological knowledge for students about the impact and influence of the internet for students, both the positive and negative impacts on students.